2011
DOI: 10.1111/j.1471-4159.2011.07278.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory and behavioural changes in the Atp7B mutant mouse model of Wilson’s disease

Abstract: Wilson's disease (WD) is caused by mutations in the copper transporting ATPase 7B (Atp7b). Patients present with liver pathology or behavioural disturbances. Studies on rodent models for WD so far mainly focussed on liver, not brain. The effect of knockout of atp7b on sensori-motor and cognitive behaviour, as well as neuronal number, inflammatory markers, copper and synaptic proteins in brain were studied in so-called toxic milk mice. Copper accumulated in striatum and hippocampus of toxic milk mice, but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…111 The morphology of mitochondria from patients with WD is altered, manifesting as separated outer and inner mitochondrial membranes, cristae dilations, and giant mitochondria; these changes occur in hepatocytes in early- and late-stage WD. 112 Although alterations in neuronal mitochondria have not been investigated in WD patients and animal models, 113 tx-j mice show neuroinflammation and develop behavioral abnormalities, 114, 115 and several animals with neuronal copper intoxication consume more oxygen, possibly indicative of mitochondrial uncoupling. 116 The structural changes in hepatocyte mitochondria might be caused by copper-induced disulfide bond (thiol)formation.…”
Section: Copper Overload Mitochondrial Function and Epigenetic Rmentioning
confidence: 99%
“…111 The morphology of mitochondria from patients with WD is altered, manifesting as separated outer and inner mitochondrial membranes, cristae dilations, and giant mitochondria; these changes occur in hepatocytes in early- and late-stage WD. 112 Although alterations in neuronal mitochondria have not been investigated in WD patients and animal models, 113 tx-j mice show neuroinflammation and develop behavioral abnormalities, 114, 115 and several animals with neuronal copper intoxication consume more oxygen, possibly indicative of mitochondrial uncoupling. 116 The structural changes in hepatocyte mitochondria might be caused by copper-induced disulfide bond (thiol)formation.…”
Section: Copper Overload Mitochondrial Function and Epigenetic Rmentioning
confidence: 99%
“…In addition, the same study reported that the cerebral zinc (Zn) concentration in 10 months animals was slightly higher than in control mice and that further iron (Fe) accumulation was found in the hippocampus of older animals. In this model, elevated concentrations of Cu were mainly found in the striatum, hippocampus and cerebellum but not in the cerebral cortex [14]. These alterations were accompanied by a mild impairment in the rotarod and cylinder tests and further by a lack of acquisition of spatial memory in the Morris water maze [14].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, inflammatory changes seemed to be restricted to microglial cells in the striatum and to astrocytes in the hippocampus. Under certain conditions, astrogliosis can be more prominent than microgliosis supported by the fact that astrocytes behave as a syncytium [22]. In animal models of AD, astrogliosis seemed to be more prevalent compared to microgliosis.…”
Section: Discussionmentioning
confidence: 99%
“…As astrocytes assist neuronal metabolism, astrocytes are expected to respond to altered neuronal functioning. For example in tauopathy models, predominantly neuronal functioning is affected but astrogliosis is more apparent and microgliosis is almost undetectable [22,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation